COINTEGRATION AND ASYMMETRIC ADJUSTMENT BETWEEN POLITICAL INSTABILITY AND ECONOMIC GROWTH: EVIDENCE FROM THAILAND - Chin-Yu Lee; Yoke-Chin Kuah; Siu-Eng Tang; Yan-Teng Tan; Chia-Guan Keh (Journal of Islamic, Social, Economics and Development, 2018)
The purpose of this paper is to empirically determine whether the cointegration and asymmetric adjustment exist in the relationship between political instability and economic growth in Thailand. Data period selected from year 1980 to 2013. Even though Threshold Autoregressive (TAR) model does not provide any evidence of cointegration between these two variables, this paper continues to carry on with Momentum Threshold Autoregressive Model (MTAR). As a finding, the asymmetric adjustment between political instability and economic growth occurred in Thailand.